Microlearning-Based Learning Video on the Content of Grade IV Elementary School Science Lesson - Pande Made Meiza Putra; Adrianus I Wayan Ilia Yuda Sukmana; I Komang Sudarma (International Journal of Natural Science and Engineering, 2024)
This research problem focuses on the limited use of technology-based learning media in schools, which affects students' low understanding of IPAS material. This research aims to create a microlearning-based learning video that is valid, practical, and effective in increasing the motivation and learning outcomes of grade IV elementary school students. This type of research is development research (R&D) with ADDIE design. The research subjects involved 31 fourth grade students and 3 experts for validation. The data collection methods used were questionnaires and tests. While the instruments used were questionnaire sheets and multiple choice tests. The data analysis process in this study involved various techniques, including qualitative, quantitative, and inferential descriptive analysis. Qualitative analysis will come from the results of questionnaires, interviews, input and criticism by experts. Meanwhile, the quantitative analysis was obtained from the calculation of the validity, practicality, and effectiveness tests of the media. Finally, hypothesis formulation and conclusions were drawn through inferential descriptive analysis. The results showed that there was a significant difference between after and before being taught using microlearning-based video media on IPAS learning content. So it can be concluded that the media developed is valid, practical, and effective to use. The results of this study are expected to be used as a reference or reference if interested in researching the use of learning media, especially microlearning-based learning videos in schools and among the community.